Las Romanticas : women writers and subjectivity in spain, 1835-1850. - Kirkpatrick, Susan (Professor of Spanish) ([Place of publication not identified] UNIV OF CALIFORNIA Press, 2022)
A pioneering critical work that establishes the existence and elaborates the history of a female literary tradition in Spain early in the nineteenth century, this book will greatly interest specialists in Spanish literature. It also addresses those concerned with Romanticism in general, with feminist criticism, and with the cultural history of women. Who were las románticas? The first generation of Spanish women to conceive of.
JSTOR
Keywords: Spanish literature -- Women authors -- History and criticism; Spanish literature -- 19th century -- History and criticism; Women and literature -- Spain -- History -- 19th century; Literature and society -- Spain; Subjectivity in literature; Romanticism -- Spain; Self in literature; Littérature espagnole -- 19e siècle -- Histoire et critique; Femmes et littérature -- Espagne -- Histoire -- 19e siècle.; Littérature et société -- Espagne; Subjectivité dans la littérature.; Romantisme -- Espagne; Moi (Psychologie) dans la littérature.; Literature and society; Romanticism; Self in literature; Spanish literature; Spanish literature -- Women authors; Subjectivity in literature; Women and literature; Spain; 1800-1899; Criticism, interpretation, etc; History